Prospects of compounds of herbal plants as anticancer agents: a comprehensive review from molecular pathways - Situmorang, Putri Cahaya; Ilyas, Syafruddin; Nugraha, Sony Eka; Syahputra, Rony Abdi; Nik Abd Rahman, Nik Mohd Afizan (Frontiers Media, 2024)
Cancer refers to the proliferation and multiplication of aberrant cells inside the human body, characterized by their capacity to proliferate and infiltrate various anatomical regions. Numerous biochemical pathways and signaling molecules have an impact on the cancer auto biogenesis process. The regulation of crucial cellular processes necessary for cell survival and proliferation, which are triggered by phytochemicals, is significantly influenced by signaling pathways. These pathways or components are regulated by phytochemicals. Medicinal plants are a significant reservoir of diverse anticancer medications employed in chemotherapy. The anticancer effects of phytochemicals are mediated by several methods, including induction of apoptosis, cessation of the cell cycle, inhibition of kinases, and prevention of carcinogenic substances. This paper analyzes the phytochemistry of seven prominent plant constituents, namely, alkaloids, tannins, flavonoids, phenols, steroids, terpenoids, and saponins, focusing on the involvement of the MAPK/ERK pathway, TNF signaling, death receptors, p53, p38, and actin dynamics. Hence, this review has examined a range of phytochemicals, encompassing their structural characteristics and potential anticancer mechanisms. It has underscored the significance of plant-derived bioactive compounds in the prevention of cancer, utilizing diverse molecular pathways. In addition, this endeavor also seeks to incentivize scientists to carry out clinical trials on anticancer medications derived from plants.